2021
DOI: 10.1002/aenm.202100875
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Novel Figure of Merit for the Assessment of Transparent Conductive Electrodes in Photovoltaics: Exact and Approximate Form

Abstract: Transparent conductive electrodes (TCEs) are key components of photovoltaic devices. Being transparent, they allow light to enter the device, and being conductive, they allow the photocurrent generated to be drawn into the outer electric circuit. Ideally, TCEs exhibit maximum light transmission and conductivity at the same time. However, both properties have to be balanced. Depending on the photovoltaic material system, the selection of the most suitable TCE is crucial and is assessed by so‐called figures‐of‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 75 publications
0
50
0
1
Order By: Relevance
“…Chu et al have demonstrated that CuNW TEs (T = 90%, R sh = 52.7 Ω sq −1 , area > 50 cm 2 ) prepared by spray coating could be assembled as resistive TSPs. [73] Flexible transparent capacitive-force detection touch sensors based on UV-curable polyurethane acrylate (PUA) resincovered CuNW electrode were also recently demonstrated by Kim et al [425] Of note, the poor adhesion of MNW networks, their nonuniform topography, and instability against static electricity Small 2022, 18, 2106006 [412] with the impact of transmittance and sheet resistance on photovoltaic performance for the spectral range of [280, 1100 nm] and a solar cell length of 5 mm. Reproduced with permission.…”
Section: Flexible Touchscreen Panels and Displaysmentioning
confidence: 99%
“…Chu et al have demonstrated that CuNW TEs (T = 90%, R sh = 52.7 Ω sq −1 , area > 50 cm 2 ) prepared by spray coating could be assembled as resistive TSPs. [73] Flexible transparent capacitive-force detection touch sensors based on UV-curable polyurethane acrylate (PUA) resincovered CuNW electrode were also recently demonstrated by Kim et al [425] Of note, the poor adhesion of MNW networks, their nonuniform topography, and instability against static electricity Small 2022, 18, 2106006 [412] with the impact of transmittance and sheet resistance on photovoltaic performance for the spectral range of [280, 1100 nm] and a solar cell length of 5 mm. Reproduced with permission.…”
Section: Flexible Touchscreen Panels and Displaysmentioning
confidence: 99%
“…recently published a figure of merit (FOM) for transparent conductive electrode (TCE) performance in solar cells. [ 1 ] Their FOM uses a detailed balance calculation for maximum power conversion efficiency of a solar cell with a given band gap ( E gap ) absorbing the air mass 1.5 global (AM1.5G) spectrum. They assume that series resistance in the TCE ( R TCE ) is [ 2,3 ] RTCEbadbreak=Rsh,TCEL23A\[ \begin{array}{*{20}{c}}{{R_{{\rm{TCE}}}} = \frac{{{R_{{\rm{sh,TCE}}}} \cdot {L^2}}}{{3 \cdot A}}}\end{array} \] …”
Section: Where To Lump Series Resistancementioning
confidence: 99%
“…Anand et al. consider monolithically integrated modules (Figure S1, Supporting Information [ 1 ] ) with cell lengths of L = 0.5 cm. However, they do not consider the optical deadspace of real monoliths, so their cells cannot be stacked side by side to form a module and their results do not scale to arbitrary areas.…”
Section: Tce Merit Is Not Universal Because It Depends On Module Arch...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ранее в 2019 г. нами была проведена оптимизация толщин оксидных слоев и серебряной прослойки для трех-слойной симметричной системы ZnO : Ga/Ag/ZnO : Ga (GAG) с целью достижения максимального критерия качества FOM (figure of merit) = T 10 av /R s (где T av -средний коэффициент оптического пропускания, R s -поверхностное сопротивление прозрачного электрода) [7]. Было показано, что трехслойная структура GAG, детали получения которой представлены в работе [8], при оптимизированных толщинах оксидных слоев d GZO = 40 nm и ультратонкого среднего слоя серебра d Ag = 10 nm (рис.…”
unclassified